Prinsip Pemuridan Rasul Paulus berdasarkan 2 Timotius 2:2: Suatu Eksposisi - Nahor Banfatin; Masye Rompa (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2022)
Discipleship is a process that shapes a person to become a disciple. Jesus Christ is the Great Teacher in making sinners as His disciples. People who have been discipled by Jesus Christ automatically have the most important responsibility to make others a disciple. The new believer needs to be accompanied to disciple them to the point where they have maturity in following Christ. The focus of this study emphasizes the content that must be prioritized in making discipleship because it is found that the focus of discipleship today places more emphasis on discipleship strategies than the content in discipleship itself. The author conducted research through literature study. There are several points of research based on the text of 2 Timothy 2:2, First, the essence of the message in discipleship. Second, the personal servant of God. Third, the command to make disciples. Fourth, the criteria of the people who are entrusted to make discipleship. Fifth, the goal of discipleship.